The availability degree of information literacy of teachers in first stage schools of Damascus Governorate - جوريه, رحاب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research intended to determine the information literacy of teachers in first stage schools of Damascus Governorate, and how changes on (ICDL certification, years of experience, academic qualification) variables effect it. To achieve the aims of the research, a descriptive analytic approach was used by designing a survey consists of 23 phrases distributed among three basic skills (access to Information, information organizing and employing, secure using of information), and a research sample consist of 428 teachers from those in first stage schools of Damascus Governorate. Research concluded to the following results: The availability degree of information literacy of teachers in first stage schools of Damascus Governorate was as following: (access to information skill has medium degree, information organizing and employing has medium degree, secure using of information skill has high degree). There’re statistically significant differences between the average responses degrees of statistical sample individuals, regarding the availability degree of information literacy based on ICDL certification variable; in favor of certified teachers. There aren’t statistically significant differences between the average responses degrees of statistical sample individuals, regarding the availability degree of information literacy based on years of experience variable. There’re statistically significant differences between the average responses degrees of statistical sample individuals, regarding the availability degree of information literacy based on academic qualification variable; in favor of higher qualification (Postgraduate Education, Educational Habilitation Diploma). There aren’t any statistical differences in the availability degree of educational and training programs design skills for postgraduate students in Faculty of Education based on gender variable.